The influence of individual and organisational factors on the intention to report sexual harassment / Ponmalar N Alagappar - Ponmalar , N Alagappar (2017)

(untitled)
Despite the fact that up to 47.3% of the workforce is now female, sexual harassment is still not recognized as a serious issue it is frequently downplayed and treated as a joke. Empirical research on sexual harassment in the recent years have indicated that up to 70% of women have experienced at least one form of sexual harassment at work. However, only a few decide to report or blow the whistle on their experience, i.e. only 1%. This is supported by studies that whistle-blowing action is not a popular means of reporting wrong-doing in Malaysian organizations. If the victims do not report their experience with sexual harassment, the offender cannot be apprehended and/or punished, and the behaviour is likely to continue. Organizations generally do not act on sexual harassment until an employee reports the problem to an organizational authority. While certainly, a variety of deterrents will be necessary to eliminate sexual harassment, a critical one is that victims report the behaviour so that some action can be taken. It appears that the decision to report a sexually harassing behaviour is a complex and difficult one, thus it is important to consider under what conditions will the target, report a sexually harassing behaviour with the inherent obstacles in doing so. In Asian countries it’s impossible to measure actual reporting rates of sexual harassment, caused by the nature of the act itself, not many are willing to disclose the fact that they have been harassed, this is evident in the number of reported cases, combined with factors such as patriarchal culture, the lack of information about sexual harassment and the conflict –avoidance tendency in collectivist countries, explains why measuring intention to report would be the nearest operational variable. There is little empirical research on intention to report sexual harassment or the applicability of the theory of planned behaviour in measuring intention to report. This study utilizes constructs and relationships from the theory of planned behaviour, in an effort to prove its effectiveness in predicting intention to report sexual harassment thus extending the application of the theory of planned behaviour to include the intention to report sexual harassment and its cross-cultural applicability. In particular, this study looks at perception of sexual harassment, organizational climate and self-efficacy as independent variables that may influence the intention to report. Using a survey data of 348 female administrators from public universities in Malaysia, the theory of planned behaviour was tested using both SPSS and Partial Least Square (version 3.0). It was revealed that the intention to report to be turned into actual reporting is at least partially determined by self-efficacy and organizational climate. The findings illustrated the powerful impact of self-efficacy is a principal factor that contributes the much-needed conviction in reporting sexual harassment. In addition, the organizational climate was a notable predictor of intention to report, which also confirms with previous studies that climate for sexual harassment, is a predictor of incidents of sexual harassment in organizations.